Comprehensive viscoelastic characterization of human lower cervical spine ligaments - Troyer, Kevin Levi, author; Puttlitz, Christian Matthew, advisor; Sakurai, Hiroshi, committee member; Heyliger, Paul Roy, 1958-, committee member (Colorado State University. Libraries, 2010)
Accurate definition of cervical spine ligament mechanical properties is requisite to understand and model global cervical spine biomechanics. These ligaments have been shown to exhibit complex nonlinear elastic behavior. In addition, ligamentous mechanical behavior is highly time-dependent (viscoelastic). Previous investigators have reported the viscoelastic stress relaxation behavior of the anterior longitudinal ligament (ALL), posterior longitudinal ligament (PLL), and ligamentum flavum (LF) of the lower cervical spine using quasi-linear viscoelastic (QLV) theory. However, QLV theory assumes that the viscoelastic behavior is independent of the applied strain magnitude. Cervical spine ligaments are subjected to multiple strain magnitudes and loading rates during physiologic loading regimes. Thus, in order to characterize the comprehensive viscoelastic behavior of cervical spine ligaments within their physiological range, and to test the validity of the use of QLV theory to model this behavior, the mechanical response of human lower cervical spine ALL, PLL, and LF was recorded from stress relaxation experiments at multiple strain magnitudes and from cyclic experiments at multiple strain amplitudes and frequencies. The ALL, PLL, and LF were dissected from the C5-C6 level of human cadaveric cervical spines. Each ligament was isolated into a bone-ligament-bone (B-L-B) preparation by removing all surrounding non-osteoligamentous tissue. Each B-L-B preparation was placed in an environmental chamber, submerged in warmed saline (37 °C), and mounted to a servo-hydraulic materials testing machine. Ligaments were subjected to a uniaxial cyclic testing protocol at multiple strain amplitudes and frequencies, as well as a stress relaxation protocol at multiple strain magnitudes. Dynamic material properties (phase shift, storage modulus, and loss modulus) were determined from the resulting load displacement data via transformation into the stress-strain space. Stress relaxation data were fitted to QLV theory and a power law formulation in order to characterize the appropriate analytic function that best described the ligament relaxation behavior. Experimental results indicated that the dynamic material properties of the ALL, PLL, and LF were dependent upon both strain amplitude and frequency. In general, the dynamic material properties of the ALL and the PLL were not statistically different, but both were statistically different form the LF. The stress relaxation data was strongly dependent on the applied strain magnitude. Also, the relaxation rate of the ALL and PLL exhibited a converging trend as strain magnitude increased, while the relaxation rate of the LF diverged with increasing strain magnitude. The different strain-dependent relaxation rate behavior of the longitudinal ligaments and the LF is possibly a result of the compositional and microstructural differences between the two ligament types. Results from both the cyclic and stress relaxation experiments indicated that QLV theory cannot adequately describe the comprehensive viscoelastic behavior of these ligaments within the physiologic loading range. Therefore, a more rigorous, fully nonlinear, viscoelastic formulation is required to model the comprehensive viscoelastic behavior of the ALL, PLL, and LF in the human lower cervical spine.
Department Head: Allan Thomson Kirkpatrick.